A psychology of choice of laws - LOW, Gary (Institutional Knowledge at Singapore Management University, 2013)
There is certainly a lot of choice going around in the market for contract law. This is a good thing, since choice is key to self-determination and may help improve our laws. Yet there may be such a thing as choice overload, and the introduction of the Common European Sales law is a timely reminder to consider its effect for the market for contract law. This article does just that. It explains what choice overload is, why it comes about, and what can be done to ameliorate its effects. The conclusion is that CESL will not cause choice overload but will not help in that respect either. Given the prospect of overload, this article evaluates the possible solutions to the problem, and advances the argument in favour of categorizing laws in order to help decision-makers to choose prudently.